Development of a joint refinement model for the spin‐resolved one‐electron reduced density matrix using different data sets. Issue 2 (1st March 2018) - Gueddida, Saber; Yan, Zeyin; Gillet, Jean-Michel
Abstract : A joint refinement model of the spin‐resolved one‐electron reduced density matrix is described and validated. The new model provides very satisfactory results. Abstract : The paper describes a joint refinement model of the spin‐resolved one‐electron reduced density matrix using simultaneously magnetic structure factors and magnetic directional Compton profiles. The model is guided by two strategies: (i) variation of basis functions and (ii) variation of the spin population matrix. The implementation for a finite system is based on an expansion of the natural orbitals on basis sets. To show the potential benefits brought by the joint refinement model, the paper also presents the refinement results using magnetic structure factors only. The joint refinement model provides very satisfactory results reproducing the pseudo‐data. In particular, magnetic Compton profiles have a strong effect not only on the off‐diagonal elements of the spin‐resolved one‐electron reduced density matrix but also on its diagonal elements.